NEXMIF overexpression is associated with autism-like behaviors and alterations in dendritic arborization and spine formation in mice - Odamah, KathrynAnn; Nishizawa Criales, Mauricio Toyoki; Man, Heng-Ye (Frontiers in Neuroscience, 2025)
We previously found that loss of the X-linked gene NEXMIF results in ASD and intellectual disability (ID). Duplication of chromosomal segments containing NEXMIF has been associated with ASD/ID in humans, but the direct link to the NEXMIF gene, as well as the behavioral and cellular consequences of NEXMIF overexpression, have not yet been explored. Here, we developed a lentivirus containing the human NEXMIF gene which was bilaterally injected into the ventricles of newborn mice. At adolescent ages, the mice were subjected to various behavioral assays to assess the presence of ASD-like behaviors and comorbidities, followed by the collection of brain tissue to examine changes in neuron morphology, protein expression, and the transcriptome. We report that NEXMIF overexpression in mice led to impaired communication, short-term memory deficits, reduced social behavior, hyperactivity, repetitive/restrictive behaviors, anxiety-like behavior, and altered nociception at adolescent ages, accompanied by attenuated dendritic spine density. RNA sequencing revealed that elevated NEXMIF dosage leads to strong dysregulation in the expression of genes involved in synaptic transmission, neuron differentiation, and post-synaptic membrane potential. Moreover, cultured neurons overexpressing NEXMIF displayed increased dendritic arborization. These findings indicate that NEXMIF overexpression results in transcriptional and cellular deficits that contribute to the development of ASD-like behaviors.